Pentagon Road Bill and Federal Highway Administrator : hearings before the United States House Committee on Public Works, Subcommittee on Roads, Eighty-Fourth Congress, second session, on July 11, 1956. (U.S. Congressional Hearings., 1956)
Committee Serial No. 84-25.